Characterization of free light chain impurity in a bispecific antibody - Monica Sadek; Neelima Mantha; Steffen Lippold; Delia Li; Kyle Spitler; Ran Li; Phillip Spinosa; Bob Liu; Steven Luu; Nicholas Woon; Yeying Zhang; Jia Guo; et al. (mAbs)
Bispecific antibodies (bsAbs) target two distinct binding sites, which enable novel mechanisms of action for the treatment of disease. Due to this structural complexity, bsAbs exhibit greater heterogeneity as compared to monospecific antibodies and may require nonstandard purification strategies to remove undesired product-related impurities. However, the implementation of unique manufacturing processes may result in the observation of new impurities. When new impurities are identified, comprehensive characterization of these species is needed to understand the potential impact to the safety and efficacy of the product. In this study, the assessment of a unique purification mode, protein L affinity chromatography, for purification of a bsAb resulted in high levels of free light chain (LC) in the final product. It was discovered that the free LC formed oligomers of various sizes upon accelerated stress in a concentration-, time-, and temperature-dependent manner. This is the first time free LC oligomer has been reported as a product-related impurity. Characterization of the free LC and free LC oligomer species was performed using a variety of chromatographic, electrophoretic, and mass spectrometry tools to gain insight on the formation and behavior of these impurities in the product. These studies informed an impact assessment of the observed free LC and free LC oligomer species on safety, immunogenicity, pharmacokinetics, and bioactivity.